2022
DOI: 10.4102/ajopa.v4i0.66
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Dispositional Hope Scale amongst South Africans: An exploratory structural equation modelling study

Abstract: Snyder’s model of hope conceptualises and operationalises hope as a cognitive, trait-like bi-dimensional future-oriented construct consisting of pathways thinking and agency thinking for goal achievement. The present study implemented exploratory structural equation modelling (ESEM) and confirmatory factor analysis (CFA) on the Dispositional Hope Scale, using data from two South African student samples (n = 383, 48% female, 21.70 years average age and n = 251, 68% female, 20.55 years average age), with the aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Furthermore, when first validating the Hope Scale, Snyder et al (1991) solely used American participants, limiting the validity of its application to other parts of the world. Khumalo and Guse (2022) examined hope within the socio-cultural context of South African samples and also underscored the importance of emphasizing one's environment on the development and expression of hope. With these two barriers to the application of Hope Theory beyond individual-focused cultures, it is unsurprising that this review found only one study from outside the Western world (Wang & Lei, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when first validating the Hope Scale, Snyder et al (1991) solely used American participants, limiting the validity of its application to other parts of the world. Khumalo and Guse (2022) examined hope within the socio-cultural context of South African samples and also underscored the importance of emphasizing one's environment on the development and expression of hope. With these two barriers to the application of Hope Theory beyond individual-focused cultures, it is unsurprising that this review found only one study from outside the Western world (Wang & Lei, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Khumalo and Guse (2022) explored the psychometric properties of the Dispositional Hope Scale (DHS) among university students in South Africa, arguing that hope is associated with several positive mental health outcomes for students and that a scale like the DHS could be used in interventions to enhance hope and consequently improve mental health for students. Interestingly, the study did not find support for the factor structure of the DHS and the model of hope on which it is based.…”
mentioning
confidence: 99%